Lei de Telecomunicações e orgão regulador no Brasil: desafios e obstáculos à luz da experência britânica e européia - Rothberg, Danilo; Kerbauy, Maria Teresa Miceli [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
A inovação tecnológica trazida pela digitalização das transmissões de rádio e TV acentua a necessidade de novos formatos de regulação e não dispensa a atuação do Estado. Diante deste contexto, deve-se considerar que a reformulação do quadro legal das comunicações no Brasil traz a possibilidade de se instituir um órgão regulador não apenas de fomento, mas de regulação e fiscalização dos serviços públicos de radiodifusão. No mundo, existem pelo menos 84 órgãos dessa natureza, em 54 países. No Reino Unido, o caso do Ofcom (Offi ce of Communications) pode trazer referências relevantes para o Brasil, que apresenta obstáculos culturais e institucionais a serem devidamente enfrentados na luta pela constituição de um serviço público de televisão nos moldes das bem-sucedidas experiências européias. Este artigo sintetiza lições trazidas pela construção do atual quadro regulatório do Reino Unido e da União Européia e analisa as barreiras à implementação deste modelo no Brasil.

The technological innovation brought by TV and radio digitalization of transmissions emphasizes the necessity of new regulation models and do not excuse the State’s action. In this context, it is important to consider that the reformulation of the legal board of communications in Brazil brings with it the possible creation of a regulation institution, not only of incitement, but of regulation and inspection of the public broadcasting services. In the world, there are at least 84 institutions like these, in 54 countries. In the United Kingdom, the Offi ce of Communications (Ofcom) case might bring relevant references to Brazil, which presents institutional and cultural obstacles that should be precisely confronted during the fi ght for the establishment of a public television service made of the models from the wellsucceeded European experiences. This article synthesizes lessons brought by the formation of the nowadays regulation board from the United Kingdom and from the European Union, also analyzing the obstacles that obstruct the establishment of his model in Brazil.
Telecommunication laws and regulator institution in Brazil: challenges and obstacles in the british and european spotlight
Keywords: Communication; Regulation; Public broadcasting service; Comunicações; Regulação; Serviço público de radiodifusão